Assessment of Primary Health Centre Information System among Health Staff - Laili Rahmatul Ilmi; Praptana Heri Herawan; Endang Purwanti; Kuswanto Harjo; Sis Wuryanto; Risa Millenia Sari; Noor Tata Afni (Technological Innovation in Engineering Research Vol. 4, 2022)
Primary health centers certainly require regional health records because this health center provides basic health services, one of which is related to coverage or needs for monitoring data. One of the health facilities that has already implemented SIMPUS is Ngaglik I Public Health Center in Sleman (an application of management information system for public health center). Clinical information systems have the potential to improve health-care facility performance, reduce operational costs, and improve patient happiness. To describe the use of SIMPUS at Ngaglik I Public Health Center and evaluate user understanding in accepting SIMPUS application based on the Technology Acceptance Model (TAM). This was a quantitative research using a survey method and analytical correlational research design. The sample consisted of 50 respondents who were selected by using a simple random sampling method. The data analysis technique was the SEM-PLS analysis technique with the TAM model and Smart-PLS software. Validity assay is carried out to test the accuracy of a measuring instrument towards any objectives to be achieved. A measurement result is said to be valid if it matches the objectives, and vice versa. The indicators for the level of validity generally use a rule of thumb to assess convergent validity and discriminant validity of measurement instruments. Statistically, the relationship between the Job Relevance and Perceived Ease of Use variables was weak (p-value = 0.818). There was a weak relationship between Output Quality and Perceived Ease of Use (p-value = 0.208). The perceived ease of use was unaffected by the users’ job relevance to SIMPUS. The perceived ease of use was unaffected by output quality. The SIMPUS display’s screen design had no effect on the intention to use it. The intention to utilise had no bearing on system usage. The intention to utilise had no bearing on system usage. The facilitation condition had no influence on system usage. The perceived ease of use and intention to use influenced system use. The capacity to demonstrate results affects perceived ease of use and intention to utilise.